Methods for the functional quantification of lysosomal membrane permeabilization: a hallmark of lysosomal cell death - Aits, Sonja (Methods Cell Biol, 2015)
Lysosomal cell death is triggered by lysosomal membrane permeabilization (LMP) and subsequent release of lysosomal hydrolases from the lysosomal lumen into the cytosol. Once released to the cytosol, the lysosomal cathepsin proteases act as executioner proteases for the subsequent cell death - either autonomously without caspase activation or in concert with the classical apoptotic machinery. Lysosomal cell death usually remains functional in apoptosis-resistant cancer cells and thus holds great potential as a therapeutic strategy for circumventing apoptosis deficiency in cancers. Notably, lysosomal cell death also plays an important role in normal physiology, e.g. during the regression of the mammary gland. Here we present four complementary methods for functional quantification and visualization of LMP during the onset of death: (1) enzymatic activity measurements of released lysosomal hydrolases in the cytosol after digitonin extraction, (2) direct visualization of LMP by monitoring the release of fluorescent dextran from lysosomes into the cytosol, (3) immunocytochemistry to detect cathepsins released into the cytosol and, (4) detection of the translocation of galectins from the cytosol to damaged lysosomes. The methods presented here can ideally be combined as needed to provide solid evidence for LMP after a given cytotoxic stimuli.